Brave New Birds: The Use of ‘Animal Integrity’ in Animal Ethics - Bovenkerk, Bernice (The Hastings Center report, 2002)
Suppose “chicken” eggs could be produced by quasi-chickens—genetically engineered humps of living chicken-flesh that do nothing but lay eggs. Would there be anything amiss with that? Animal ethicists invoke the notion of animal integrity in order to give intellectual content to the intuition that there would be. On inspection, ‘integrity’ isn't everything its proponents want it to be. Yet there's enough in it to make reasoned argument possible.